The problem of cross risk of arterial hypertension progression, obstructive sleep apnea syndrome and COVID-19 - К. A. Popov; Yu. V. Bulaeva; S. A. Ermasova; Yu. G. Shvarts (Российский кардиологический журнал)
This review considers the risk factors for arterial hypertension (AH) progression, obstructive sleep apnea syndrome (OSAS) and novel coronavirus infection (COVID-19) as potential variables for the prognostic models of estimating the probability of destabilization of the mentioned conditions. The most published studies consider AH and OSAS as the risk factors influencing the course of COVID-19, while moderate and mild COVID-19 can be destabilizing factor regarding to AH and OSAS. In addition, COVID-19, AH and OSAS are interrelated with sleep quality. The worsening of sleep quality often can be both a consequence of these diseases and a factor aggravating their course, and also can cause the increased vulnerability to acute diseases. An increased body mass index is a universal risk factor for many diseases and clinical conditions, and the monitoring of body mass increases the degree of the control of the diseases associated with obesity. In addition, the worsening of sleep quality can be both a consequence of any of above-mentioned conditions and a factor aggravating their course. Also, a promising direction for improving prognostic models is the analysis of autonomic dysfunction in patients.